High-rigidity iron-based alloy and its manufacturing method
Patent Information
- Application Number
- JP2021139912
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-30
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-08-30
AI Technical Summary
【0013】 本発明により、容易に機械加工することができる高剛性鉄基合金、及びその製造方法が提供される。
Smart Images

Figure 0007633126000001 
Figure 0007633126000002 
Figure 0007633126000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-stiffness iron-based alloy that includes a matrix made of iron or an iron alloy and fine titanium boride dispersed in the matrix, and to a method for producing the high-stiffness iron-based alloy by an additive manufacturing method. [Background technology]
[0002] Currently, steel and iron alloys are the most widely used structural metal materials. These metal materials can exhibit a wide variety of structural changes through the addition of alloying elements and heat treatment, and their mechanical properties, such as strength, toughness, and ductility, can be widely controlled.
[0003] For example, Patent Document 1 describes a non-heat treated steel component having a structure consisting of ferrite and pearlite, the non-heat treated steel component having a columnar structure consisting of a band-shaped pearlite layer having a width of 200 μm or less extending in the longitudinal direction of the non-heat treated steel component, and a ferrite layer precipitated between the pearlite layers and extending in the longitudinal direction, and a method for manufacturing the same.
[0004] On the other hand, rigidity, which is important in the design of actual parts, is a value specific to a material that is directly related to the bonding strength between atoms, so it has been thought to be difficult to significantly improve rigidity.
[0005] Under these circumstances, research and development has been conducted on dispersing compound particles such as borides with a high Young's modulus in iron or iron alloys with the aim of increasing rigidity. For example, Patent Document 2 describes a highly rigid iron-based alloy that comprises a matrix made of iron or an iron alloy and at least one or more types of borides mainly made of Group 4A elements that are dispersed in the matrix and have particle sizes of 1 to 100 μm, and that are characterized in that the borides mainly made of Group 4A elements are thermodynamically stable in the matrix. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-203148 A [Patent Document 2] JP 2002-285303 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the high-rigidity iron-based alloy described in Patent Document 2, for example, the crystal grains of the matrix made of iron or iron alloy are large, and the high-hardness borides dispersed in the matrix are also coarse, which may destroy cutting tools during machining such as cutting.
[0008] Therefore, an object of the present invention is to provide a highly rigid iron-based alloy that can be easily machined, and a method for producing the same. [Means for solving the problem]
[0009] The factors that cause the crystal grains and borides in the matrix of a high modulus iron-based alloy to become coarse include excessive heat applied during the production of the high modulus iron-based alloy, the difficulty of obtaining a homogeneous mixture by mixing the iron or iron alloy powder that constitutes the matrix of the high modulus iron-based alloy with a boride powder having a small particle size, for example, a boride powder having an average particle size of 1 μm or less, and further, when the powder mixture is melted, the originally fine borides aggregate and bond together, causing them to become larger.
[0010] The inventors have investigated various means for solving the above-mentioned problems and have found that it is possible to produce a high-rigidity iron-based alloy in which small grain borides are formed in a matrix of small crystal grains by generating borides through an in-situ reaction in a matrix made of iron or an iron alloy and controlling the thermal history so that the generated borides do not undergo excessive crystal growth, or by irradiating a material containing iron, boron, and titanium with an electron beam (EB).
[0011] As a result of further investigation, the inventors have found that a high-rigidity iron-based alloy containing a matrix made of iron or iron alloy with small crystal grains and fine titanium boride dispersed in the matrix can be produced by treating, with an electron beam, a mixed powder obtained by mixing a material containing iron, boron, and titanium, for example, a powder of an iron-titanium intermetallic compound (FeTi) and a powder of an iron boride intermetallic compound (FeB), or a cast body and / or a sintered body and / or a laminate containing iron and titanium boride. Thus, the present invention has been completed.
[0012] That is, the gist of the present invention is as follows. (1) A high-stiffness iron-based alloy comprising a matrix of iron or an iron alloy and titanium boride dispersed in the matrix, A high-rigidity iron-based alloy in which the average circle-equivalent grain size of the matrix in an IPF image is 1 μm or less. (2) The high-rigidity iron-based alloy according to (1), wherein the titanium boride has an average circle-equivalent grain size of 0.01 μm to 0.2 μm in an SEM image. (3)(i) providing a material containing iron, boron, and titanium; and (ii) A process for treating the material prepared in step (i) with an electron beam to obtain a high-rigidity iron-based alloy. 1. A method for producing a high stiffness iron-based alloy, comprising: (4) A method for producing a high-rigidity iron-based alloy according to (3), wherein in the step (i), the material containing iron, boron, and titanium is a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound with a powder of an iron boride intermetallic compound. (5) A method for producing a high-rigidity iron-based alloy according to (4), wherein in the step (ii), the treatment with an electron beam is an additive manufacturing method involving electron beam irradiation. (6) A method for producing a high-rigidity iron-based alloy according to (5), wherein in the step (ii), the additive manufacturing method involving electron beam irradiation is a PBF method. (7) A method for producing a high-rigidity iron-based alloy according to (3), wherein in step (i), the material containing iron, boron, and titanium is a cast body and / or a sintered body and / or a laminate containing iron and titanium boride. Effect of the Invention
[0013] The present invention provides a highly rigid iron-based alloy that is easily machined and a method for its manufacture. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram showing how titanium boride (TiB2) is formed by irradiating an electron beam to a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound (FeTi) and a powder of an iron boride intermetallic compound (FeB) in step (ii) of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing an example of an apparatus for carrying out an additive manufacturing method using a PBF method. [Diagram 3] FIG. 1 is a schematic diagram showing an example of an apparatus for carrying out an additive manufacturing method using a DED method. [Figure 4] FIG. 2 is a schematic diagram of a test piece obtained in Example 1. [Diagram 5] 1A) IPF image and B) SEM image of Example 1. [Figure 6] 13 is an IPF image of Example 2. [Figure 7] FIG. 11 is a diagram showing a schematic diagram of a change in the structure of a site irradiated with an electron beam in Example 2. [Figure 8] 1 is a graph showing the relationship between the electron beam irradiation output and the Vickers hardness of the irradiated castings 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Preferred embodiments of the present invention will now be described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. In the drawings, the dimensions and shapes of each part are exaggerated for clarity, and the actual dimensions and shapes are not accurately depicted. Therefore, the technical scope of the present invention is not limited to the dimensions and shapes of each part shown in these drawings. The high-rigidity iron-based alloy of the present invention and its manufacturing method are not limited to the following embodiments, and can be embodied in various forms with modifications and improvements that can be made by those skilled in the art, without departing from the gist of the present invention.
[0016] The present invention relates to a high-stiffness iron-based alloy that includes a matrix made of iron or an iron alloy and titanium boride dispersed in the matrix, the matrix having a crystal grain size within a specific range.
[0017] Here, the high-rigidity iron-based alloy of the present invention has a structure in which fine titanium borides are uniformly dispersed in a matrix made of iron or an iron alloy.
[0018] A wide range of iron alloys can be used as the iron alloy that constitutes the matrix of the high-rigidity iron-based alloy of the present invention, including ferritic, austenitic, and martensitic alloys, and from the viewpoint of thermodynamic stability, it is preferable that the carbon content is 0.1 wt % or less.
[0019] In the high-rigidity iron-based alloy of the present invention, the circle-equivalent average grain size of crystal grains in an IPF image of a matrix made of iron or an iron alloy is 1 μm or less, preferably 0.1 μm to 0.5 μm.
[0020] The method for measuring the average circle-equivalent diameter of crystal grains using an IPF image of a matrix made of iron or an iron alloy can be performed by first taking three EBSD (Electron Back Scattered Diffraction Pattern)-IPF (Inverse Pole Figure) images of the high-rigidity iron-based alloy to be measured, then randomly selecting 30 crystal grains in each image, calculating the area of each selected crystal grain, calculating the circle-equivalent diameter from the calculated areas, and finally taking the arithmetic mean value of the calculated circle-equivalent diameters.
[0021] By having the average grain size of the crystal grains of the matrix made of iron or iron alloy within the above range, when machining a high-rigidity iron-based alloy, the stress applied to the cutting tool in cutting high-hardness titanium boride is dispersed, fracture of the cutting tool is reduced, and machinability is improved while maintaining high rigidity.
[0022] The titanium boride uniformly dispersed in the matrix of iron or an iron alloy of the high-modulus iron-based alloy of the present invention is a diboride represented by the chemical formula TiB2.
[0023] The titanium boride contained in the high-rigidity iron-based alloy of the present invention has a regular crystal structure and is a compound in which the constituent atoms are strongly bonded, so that the Young's modulus, which directly reflects the bonding force, is extremely high. Furthermore, since titanium boride is thermodynamically stable in an iron alloy, it does not undergo crystallographic changes due to the reaction between titanium boride and a matrix made of iron or an iron alloy, such as the intrusion or substitution of a different atom or the formation of another complex compound. As a result, titanium boride maintains a strong bonding force even in an iron alloy, does not change with its high Young's modulus, and can fully demonstrate its excellent properties as a reinforcing particle that contributes to the high rigidity of the iron-based alloy. Therefore, the iron-based alloy of the present invention can have an extremely high Young's modulus.
[0024] The average particle size of titanium boride, as the circle-equivalent average particle size in an SEM image, is usually 0.01 μm to 1 μm, preferably 0.01 μm to 0.2 μm, and more preferably 0.01 μm to 0.1 μm.
[0025] The method for measuring the average circle-equivalent particle size using SEM images of titanium boride can be performed by first taking three BSE-SEM images (backscattered electron images) of the high-rigidity iron-based alloy to be measured, then randomly selecting 300 titanium borides in each image, calculating the area of each selected titanium boride, calculating the circle-equivalent diameter from the calculated areas, and finally taking the arithmetic mean value of the calculated circle-equivalent diameters.
[0026] By having the average particle size of the titanium boride within the above range, when machining a high-rigidity iron-based alloy, the stress applied to the cutting tool when cutting the high-hardness titanium boride is dispersed, thereby reducing breakage of the cutting tool and improving machinability while maintaining high rigidity.
[0027] The particle size of the titanium boride is preferably uniform. The particle size of the titanium boride is not limited, but for example, when the titanium boride particles follow a normal distribution, 68% of the number of the titanium boride particles are usually within the range of the average particle size ±0.1 μm, preferably the average particle size ±0.05 μm.
[0028] By making the grain size of the titanium boride uniform, the stress applied to the cutting tool when cutting the high-hardness titanium boride is dispersed when machining high-rigidity iron-based alloys, reducing breakage of the cutting tool and improving machinability while maintaining high rigidity.
[0029] The content of titanium boride is usually 3 volume % to 40 volume %, and preferably 7 volume % to 35 volume %, relative to the total volume of the high-rigidity iron-based alloy.
[0030] By having the titanium boride content within the above range, the titanium boride does not aggregate or coalesce with other borides, and the high-rigidity iron-based alloy can exhibit sufficient mechanical properties, particularly high rigidity.
[0031] Therefore, the high-rigidity iron-based alloy of the present invention exhibits sufficient mechanical properties, particularly high rigidity, due to the presence of titanium boride, and further, due to the fineness of the titanium boride and the small crystal grains of the matrix made of iron or iron alloy, it can be easily cut in the cutting process without destroying the cutting tool.
[0032] In addition to titanium boride, the high modulus iron-base alloy of the present invention may contain one or more other elements, such as nickel, cobalt, chromium, magnesium, molybdenum, carbon, manganese, and compounds thereof, such as borides, depending on the components required in the final high modulus iron-base alloy.
[0033] Furthermore, the present invention also relates to a method for producing the high modulus iron-based alloy of the present invention described above, that is, the method for producing a high modulus iron-based alloy includes the steps of (i) preparing a material containing iron, boron, and titanium, and (ii) treating the material prepared in the step (i) with an electron beam to obtain a high modulus iron-based alloy.
[0034] Each of steps (i) and (ii) will be described below.
[0035] (i) preparing a material containing iron, boron and titanium; In step (i) of the present invention, a material containing iron, boron and titanium is prepared.
[0036] An example of a material containing iron, boron, and titanium is a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound with a powder of an iron boride intermetallic compound.
[0037] Iron-titanium intermetallic powder is a milled powder of an alloy containing iron and titanium (FeTi).
[0038] The average particle size of the powder of the iron-titanium intermetallic compound is not limited, but is usually 25 μm to 200 μm, and preferably 45 μm to 140 μm, as D50 in the volume-based particle size distribution measured by a laser diffraction / scattering method.
[0039] By setting the average particle size of the iron-titanium intermetallic compound powder within the above range, it is possible to easily and uniformly mix it with the iron boride intermetallic compound powder.
[0040] The composition of the iron-titanium intermetallic compound can be changed depending on the amount of titanium boride contained in the high-rigidity iron-based alloy being produced, but the weight ratio of iron to titanium (Fe:Ti) is usually adjusted to be 80:20 to 25:75, preferably 70:30 to 50:50.
[0041] By making the composition of the iron-titanium intermetallic compound fall within the above range, a stable iron-titanium intermetallic compound can be obtained, and the amount of titanium boride described above can be ensured in the final high-rigidity iron-based alloy through reaction with the iron boride intermetallic compound.
[0042] Iron boride intermetallic powder is a milled powder of an alloy containing iron and boron (FeB).
[0043] The average particle size of the powder of the iron boride intermetallic compound is not limited, but is usually 25 μm to 200 μm, and preferably 45 μm to 140 μm, as D50 in the volume-based particle size distribution measured by a laser diffraction / scattering method.
[0044] By setting the average particle size of the iron boride intermetallic compound powder within the above range, it is possible to easily and uniformly mix it with the iron titanium intermetallic compound powder.
[0045] The composition of the iron boride intermetallic compound can be changed depending on the amount of titanium boride contained in the high-rigidity iron-based alloy to be produced, but the weight ratio of iron to boron (Fe:B) is usually adjusted to be 95:5 to 70:30, preferably 85:15 to 75:25.
[0046] By setting the composition of the iron boride intermetallic compound within the above range, a stable iron boride intermetallic compound can be obtained, and the amount of titanium boride described above can be ensured in the finally obtained high-rigidity iron-based alloy through reaction with the iron titanium intermetallic compound.
[0047] The iron-titanium intermetallic compound powder and the iron boride intermetallic compound powder may contain one or more other elements, such as nickel, cobalt, chromium, magnesium, molybdenum, carbon, manganese, etc., depending on the components required in the final high-rigidity iron-based alloy.
[0048] The mixing ratio of the iron-titanium intermetallic compound powder and the iron boride intermetallic compound powder can be changed depending on the composition of each material and the amount of titanium boride contained in the high-rigidity iron-based alloy to be manufactured. For example, the weight ratio of the iron-titanium intermetallic compound powder and the iron boride intermetallic compound powder (FeTi:FeB) is usually 75:25 to 25:75, preferably 60:40 to 40:60. Alternatively, the mixing ratio of the iron-titanium intermetallic compound powder and the iron boride intermetallic compound powder is adjusted so that the weight ratio of titanium to boron (Ti:B) is usually 1:1 to 10:1, preferably 1.5:1 to 2.5:1.
[0049] By setting the mixing ratio of the iron-titanium intermetallic compound powder and the iron boride intermetallic compound powder within the above-mentioned range, the iron-titanium intermetallic compound and the iron boride intermetallic compound react sufficiently in the matrix made of iron or iron alloy, and the amount of titanium boride described above can be secured in the finally obtained high-rigidity iron-based alloy.
[0050] In step (i), depending on the components required in the final high-rigidity iron-based alloy, one or more other elements, such as nickel, cobalt, chromium, magnesium, molybdenum, carbon, manganese, etc., may be mixed.
[0051] The order and method of mixing each powder, i.e., the powder of the iron-titanium intermetallic compound, the powder of the iron boride intermetallic compound, and the powder containing one or more other elements, are not limited, and they can be mixed using a mixing means known in the art. For example, when the mixed powder contains a powder containing one or more other elements, the powder of the iron-titanium intermetallic compound and the powder of the iron boride intermetallic compound may be mixed and then the powder containing one or more other elements may be mixed, the powder of the iron-titanium intermetallic compound and the powder containing one or more other elements may be mixed and then the iron boride intermetallic compound may be mixed, the powder of the iron boride intermetallic compound and the powder containing one or more other elements may be mixed and then the iron-titanium intermetallic compound may be mixed, or all the powders may be mixed at the same time. Examples of the method of mixing each powder include a V-type mixer (V-type powder mixer), a ball mill, and a vibration mill. The powders may be mixed by wet mixing.
[0052] By the step (i) of the present invention, it is possible to obtain a mixed powder in which a powder of an iron-titanium intermetallic compound, a powder of an iron boride intermetallic compound, and optionally a powder containing one or more other elements are uniformly dispersed.
[0053] Further, the material containing iron, boron and titanium includes a cast body and / or a sintered body and / or a laminated body containing iron and titanium boride.
[0054] For example, a casting containing iron and titanium boride can be obtained by mixing a powder of the iron-titanium intermetallic compound described above, a powder of the iron boride intermetallic compound, and optionally a powder containing one or more other elements, heating the resulting mixed powder to a temperature equal to or higher than the melting temperature of each powder, and then cooling the mixture.
[0055] For example, a sintered body containing iron and titanium boride can be obtained by mixing a powder of the iron-titanium intermetallic compound described above, a powder of the iron boride intermetallic compound, and optionally a powder containing one or more other elements, to obtain a mixed powder, firing (sintering) the mixed powder at a temperature below the melting temperature of each powder, and then cooling the mixture.
[0056] For example, a laminate containing iron and titanium boride can be obtained by mixing a powder of the iron-titanium intermetallic compound described above, a powder of the iron boride intermetallic compound, and optionally a powder containing one or more other elements, to obtain a mixed powder, and processing the mixed powder by an additive manufacturing method involving laser irradiation.
[0057] Here, the additive manufacturing method involving laser irradiation is a method in which a laser is irradiated onto a mixed powder material to melt and solidify only specific portions, and this process is repeated to mold the alloy without a mold. Laser irradiation may be performed based on slice data converted from 3D data.
[0058] The additive manufacturing method involving laser irradiation enables rapid heating, convection stirring, and rapid cooling of the mixed powder.
[0059] The additive manufacturing method involving laser irradiation can be carried out by replacing the electron beam with a laser in the additive manufacturing method involving electron beam irradiation described below, and further changing the vacuum atmosphere to an argon-substituted environment.
[0060] (ii) A process for treating the material prepared in step (i) with an electron beam to obtain a high-rigidity iron-based alloy. In step (ii), the material prepared in step (i) is treated with an electron beam to obtain a high-rigidity iron-based alloy.
[0061] When the material prepared in step (i) is a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound with a powder of an iron boride intermetallic compound, the material prepared in step (i) is processed by an additive manufacturing method involving electron beam irradiation to obtain a high-rigidity iron-based alloy.
[0062] In the step (ii) of the present invention, the additive manufacturing method involving electron beam irradiation is a method in which an electron beam is irradiated onto a mixed powder material to melt and solidify only specific portions, and this process is repeated to mold an alloy without a mold. Note that the electron beam irradiation may be performed based on slice data converted from 3D data.
[0063] An electron beam is a beam of accelerated electrons.
[0064] The additive manufacturing method involving electron beam irradiation enables rapid heating, convection mixing, and rapid cooling of the mixed powder.
[0065] In a manufacturing method of an iron-based alloy in which titanium boride is formed in a matrix made of iron or an iron alloy using powders of an iron-titanium intermetallic compound and powders of an iron boride intermetallic compound as materials, when sintering is used, titanium boride is formed by solid-phase diffusion during the heating and sintering process in sintering the mixed powder, and then grows. Since the longer the time that the particles are in an environment in which they can grow, in order to obtain fine titanium boride and a matrix with small crystal grains, it is preferable to shorten the time during which titanium boride can grow after the nucleation of titanium boride and the time during which the crystal grains of the matrix can grow, that is, the time until the material solidifies. Therefore, in the present invention, by using an additive manufacturing method involving electron beam irradiation to form titanium boride in a matrix made of iron or an iron alloy using powders of an iron-titanium intermetallic compound and powders of an iron boride intermetallic compound, the cooling rate after powder melting can be increased, that is, the time for particle (crystal) growth after the nucleation of titanium boride and the time for crystal grain growth of the matrix can be shortened. Furthermore, the titanium boride particles have a pinning effect on the crystal grains of the matrix, causing the matrix to be refined. As a result, a highly rigid iron-based alloy can be formed in which small grain borides are formed in a matrix of small crystal grains, which achieves both high rigidity and high strength and also improves elongation relative to strength, as a result of the synergistic effect of the refinement of the crystal grains of the titanium boride and matrix due to the shortened time until the material solidifies, and the refinement of the crystal grains of the matrix due to the pinning effect of the fine titanium boride.
[0066] FIG. 1 shows a schematic diagram of the process in step (ii) of the present invention in which titanium boride (TiB2) is formed by irradiating an electron beam onto a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound and a powder of an iron boride intermetallic compound.
[0067] Figure 1 shows how, when an electron beam is irradiated to a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound and a powder of an iron boride intermetallic compound, the mixed powder melts and TiB2 nuclei are formed in a matrix made of iron or an iron alloy, and then TiB2 grows above the growth temperature of TiB2, and when the temperature falls below the growth temperature of TiB2, the growth of TiB2 stops and the structure is determined. In the electron beam treatment, the mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound and a powder of an iron boride intermetallic compound can absorb the energy of the electron beam without loss regardless of whether it is in a powdered state or a molten state, so that excessive absorption of energy is suppressed, and therefore excessive growth of TiB2 can be suppressed.
[0068] Additive manufacturing methods involving electron beam irradiation include, for example, Powder Bed Fusion (PBF).
[0069] PBF is a method in which mixed powder is spread out, the part to be shaped is irradiated with an electron beam, and the alloy is molded by melting, solidifying, and layering it.
[0070] In PBF, alloy precursors melted by electron beam irradiation can be rapidly cooled, typically at a rate of 10,000 K / sec or more, to produce the alloy.
[0071] Figure 2 is a schematic diagram of an example of an apparatus for implementing additive manufacturing using the PBF method. In Figure 2, first, mixed powder 1 loaded into a raw material container is pushed up inside a cover 7 for creating a vacuum atmosphere, and the pushed-up portion of the mixed powder 1 is spread out by a blade 2. Next, an electron beam 4 is irradiated by an electron beam generator 3 onto the mixed powder 1 spread out by the blade 2. When the electron beam 4 is irradiated onto the mixed powder 1, the powder particles in the mixed powder 1 melt and bond together, forming an iron-based alloy 5 on a base plate 6. These steps are repeated while the base plate 6 is lowered (additive manufacturing), and the iron-based alloy 5 is molded.
[0072] In the step (ii) of the present invention, a powder of an iron-titanium intermetallic compound and a powder of an iron boride intermetallic compound are reacted in situ to produce fine titanium boride uniformly dispersed in a matrix of iron or iron alloy having small crystal grains, thereby making it possible to obtain a high-rigidity iron-based alloy with excellent machinability.
[0073] When the material prepared in step (i) is a casting and / or a sintered body and / or a laminate containing iron and titanium boride, the material prepared in step (i) is treated with an electron beam to obtain a high-rigidity iron-based alloy.
[0074] In electron beam treatment, cast bodies and / or sintered bodies and / or laminates containing iron and titanium boride, regardless of whether they are in a powdered or molten state, absorb the energy of the electron beam without loss, forming a matrix with small crystal grains, and by decomposing and diffusing coarse titanium boride, fine titanium boride can be formed.
[0075] In addition to irradiating an electron beam to a target portion of a material where high stiffness and strength are required, electron beam processing also includes, for example, additive manufacturing methods involving electron beam irradiation, such as Directed Energy Deposition (DED).
[0076] DED is a method in which an electron beam is irradiated onto a wire-shaped material formed of a cast and / or sintered body and / or laminate containing iron and titanium boride, and the wire is melted and laminated to create a shape. It is also called build-up welding.
[0077] In DED, alloy precursors melted by irradiation with an electron beam are rapidly cooled, typically at a rate of around 10,000 K / sec, to produce the alloy.
[0078] Fig. 3 is a schematic diagram of an example of an apparatus for carrying out additive manufacturing using the DED method. In Fig. 3, a wire-shaped material 8 is placed on a base 10, and an electron beam 4 generated by an electron beam generator 3 is irradiated onto the wire-shaped material 8. When the electron beam 4 is irradiated onto the wire-shaped material 8, the wire-shaped material 8 melts and bonds with itself, and an iron-based alloy 5 is formed on the base 10. These steps are repeated while the modeling platform 9 is lowered (additive modeling), and the iron-based alloy 5 is molded.
[0079] Since the material prepared in step (i) is a cast and / or sintered body and / or laminate containing iron and titanium boride, the electron beam can be irradiated only to the target portion of the material, that is, only the target portion of the iron-based alloy, for example, the stress concentration portion, exhibits sufficient mechanical properties, particularly high rigidity, and furthermore, since the titanium boride is fine and the crystal grains of the matrix made of iron or iron alloy are small, it is possible to give the property of being able to cut easily without destroying the cutting tool in the cutting process. Therefore, it is possible to reduce costs and improve mass productivity compared to irradiating the entire material with an electron beam. In addition, in the electron beam irradiation, the strength is different between the center and the edge of the electron beam irradiated portion, and the strength of the center of the electron beam irradiated portion is higher than that of the edge, so that no distortion occurs at the boundary between the portion irradiated with the electron beam and the portion not irradiated with the electron beam. EXAMPLES
[0080] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0081] 1. Sample Preparation Example 1 An iron-based alloy was produced by the following steps (i) and (ii).
[0082] (i) preparing a material containing iron, boron and titanium; In step (i), a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound (FeTi) and a powder of an iron boride intermetallic compound (FeB) was used as the material containing iron, boron, and titanium.
[0083] The mixed powder was obtained by mixing a crushed powder of 57% by weight Fe and 43% by weight Ti as an iron-titanium intermetallic compound powder (particle size (D50): 45 μm to 140 μm as measured by laser diffraction and scattering) and a crushed powder of 78% by weight Fe and 22% by weight B as an iron boride intermetallic compound powder (particle size (D50): 45 μm to 140 μm as measured by laser diffraction and scattering) so that the weight ratio of FeTi to FeB was 1:1, and mixing them in a V-type mixer for 30 minutes.
[0084] (ii) A process of processing the material prepared in step (i) by a layered forming method (PBF method) involving electron beam irradiation to obtain an iron-based alloy. In step (ii), the mixed powder prepared in step (i) was treated under the following conditions in a vacuum atmosphere using the apparatus shown in FIG. 2 to obtain a disk-shaped iron-based alloy (Fe / 30 vol% TiB2) having a diameter of 20 mm and a height of 3 mm, as shown diagrammatically in FIG. 4. PBF conditions Electron beam power: 300W Scan speed: 1000mm / sec Beam diameter: 0.2mm Lamination thickness: 0.09mm Cooling rate: 10000K / sec or more Here, the laminate thickness is the thickness per layer.
[0085] Example 2 An iron-based alloy was produced by the following steps (i) and (ii).
[0086] (i) preparing a material containing iron, boron and titanium; In step (i), a casting containing iron and titanium boride (a casting obtained by mixing powders of pure Fe, pure Cr, pure Ti, and Fe-B to give a ratio of 30 vol% TiB2 / Fe-17 mass% Cr and high-frequency melting, Fe-17mass%Cr / 30vol%TiB2) was prepared as a material containing iron, boron, and titanium.
[0087] (ii) A process for treating the material prepared in step (i) with an electron beam to obtain an iron-based alloy. In step (ii), the casting prepared in step (i) was irradiated with an electron beam in a vacuum atmosphere under the following conditions to obtain an iron-based alloy. Electron beam irradiation conditions Electron beam power: 1800W Scan speed: 500mm / sec Beam diameter: 0.3mm Lamination thickness: 0.07mm Cooling rate: 10000K / sec or more
[0088] 2. EBSD-IPF and BSE-SEM Image Evaluation An EBSD-IPF image and a BSE-SEM image were taken of the iron-based alloy obtained in Example 1, and an EBSD-IPF image was taken of the iron-based alloy obtained in Example 2. Figure 5 shows the results of Example 1 [A) IPF image, B) SEM image (black is TiB2)], and Figure 6 shows the results of Example 2. In Figure 6, the material before the electron beam irradiation is shown as the as-cast material, and the part irradiated with the electron beam is shown as the EB irradiated part.
[0089] 5, it was found that in Example 1, a high-rigidity iron-based alloy in which fine titanium boride particles of 0.2 μm or less are present on the periphery of crystal grains of an Fe-based matrix having an average circle-equivalent grain size of 1 μm or less can be produced by irradiating an electron beam onto a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound and a powder of an iron boride intermetallic compound. 6, it was found that in Example 2, a high-rigidity iron-based alloy in which titanium boride particles of small grain size are formed in an Fe-based matrix having small grains can be produced by irradiating an electron beam onto a cast containing iron and titanium boride.
[0090] Furthermore, in Example 2, it was found that by irradiating a certain portion of a casting containing iron and titanium boride with an electron beam, only the portion irradiated with the electron beam can be made into a high-rigidity iron-based alloy in which titanium boride with small grain size is formed in an Fe-based matrix with small crystal grains. A schematic diagram of Example 2 is shown in Figure 7.
[0091] 3. Machinability evaluation The iron-based alloys obtained in Examples 1 and 2 were cut using a general-purpose grindstone (wet type). The iron-based alloys of Examples 1 and 2 had low resistance and could be cut without any problems.
[0092] 4. Vickers hardness evaluation The Vickers hardness was measured for two types of iron-based alloys containing iron and titanium boride (Casting 1: a casting made by mixing powders of pure Fe, pure Cr, pure Ti, and Fe-B to give a composition of 15 vol% TiB2 / Fe-17 mass% Cr and high-frequency melting (Fe-17mass%Cr / 15vol%TiB2); Casting 2: a casting made by mixing powders of pure Fe, pure Cr, pure Ti, and Fe-B to give a composition of 30 vol% TiB2 / Fe-17 mass% Cr and high-frequency melting (Fe-17mass%Cr / 30vol%TiB2)) and changing the output of the electron beam.
[0093] The results are shown in Figure 8. Figure 8 shows that the Vickers hardness increases by 200% to 300% by irradiating with the electron beam compared to before irradiation, that the rate of increase in Vickers hardness is greater for casting 2 than for casting 1 (this is believed to be because the structure of the iron-based alloy is homogenized by electron beam irradiation, resulting in a more pronounced increase in strength with an increase in TiB2 content), and that the Vickers hardness decreases as the output of the electron beam increases. [Explanation of symbols]
[0094] 1. Mixed powder, 2. Blade, 3. Electron beam generator, 4. Electron beam, 5. Iron-based alloy, 6. Base plate, 7. Cover, 8. Wire-like material, 9. Build platform, 10. Substrate
Claims
1. A high-stiffness iron-based alloy comprising a matrix of iron or an iron alloy and titanium boride dispersed in the matrix, the average circle-equivalent grain size of the crystal grains in the IPF image of the matrix is 0.1 μm to 0.5 μm, and the average circle-equivalent grain size of the crystal grains in the IPF image of the matrix is calculated by first taking three EBSD-IPF images of the high-rigidity iron-based alloy to be measured, then randomly selecting 30 crystal grains in each image, then calculating the area of each selected crystal grain, calculating the circle-equivalent diameter from the calculated areas, and finally taking an arithmetic average of the calculated circle-equivalent diameters; The average circle-equivalent particle size in the SEM image of titanium boride is 0.01 μm to 0.2 μm, and the average circle-equivalent particle size in the SEM image of titanium boride is calculated by first taking three BSE-SEM images of the high-rigidity iron-based alloy to be measured, then randomly selecting 300 titanium borides in each image, then calculating the area of each selected titanium boride, calculating the circle-equivalent diameter from the calculated area, and finally taking an arithmetic average value of the calculated circle-equivalent diameters. High-rigidity iron-based alloy.
2. (i) preparing a material containing iron, boron and titanium, the material containing iron, boron and titanium being a mixed powder obtained by mixing a powder of an iron-titanium intermetallic compound and a powder of an iron boride intermetallic compound; (ii) A step of treating the material prepared in step (i) with an electron beam to obtain a high-rigidity iron-based alloy, the treatment with the electron beam being an additive manufacturing method involving electron beam irradiation of the PBF method.
1. A method for producing a high stiffness iron-based alloy, comprising:
3. (i) preparing a material containing iron, boron and titanium, the material containing iron, boron and titanium being a cast body and / or a sintered body and / or a laminate containing iron and titanium boride; and (ii) A step of treating the material prepared in step (i) with an electron beam to obtain a high-rigidity iron-based alloy, the electron beam treatment being an additive manufacturing method involving electron beam irradiation of the DED method.
1. A method for producing a high stiffness iron-based alloy, comprising:
Citation Information
Patent Citations
High rigidity iron based alloy and production method therefor
JP2002285303A
Titanium boride-containing powder and manufacturing method therefor and manufacturing method of sintered metal
JP2017088972A
Non-heat-treated steel member and manufacturing method therefor
JP2019203148A
Powder for molding laminate, laminate molded body, and manufacturing method of laminate molded body
JP2020084294A
Integrally-molded component, iron alloy powder and method for producing integrally-molded component
JP2021066933A